2012
DOI: 10.1007/s10900-012-9593-5
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Stress and its Impact on Health in Poor Communities

Abstract: With the increased understanding of the relationship between stress and disease, the role of stress in explaining persistent disparities in health outcomes has received growing attention. One body of research has focused on allostatic load--the "wear and tear" that results from chronic or excessive activation of the stress response. Other research has looked at the link between stress and health behaviors. In this study, we conducted 7 focus groups with a total of 56 people to understand how people living in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 38 publications
3
31
0
4
Order By: Relevance
“…Perceived stress may constitute a barrier for the prevention of smoking initiation and also for the achievement of smoking cessation. Focus group research among low-income people in New York suggested that perceived stress reinforces unhealthy behaviours including smoking, which in turn act as a short term solution to aid in the ‘management’ of their stress 38 . However, despite concerns of a potential deterioration in stress, studies have found that even among highly dependent smokers, stopping smoking is not associated with any long term increases in perceived stress 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Perceived stress may constitute a barrier for the prevention of smoking initiation and also for the achievement of smoking cessation. Focus group research among low-income people in New York suggested that perceived stress reinforces unhealthy behaviours including smoking, which in turn act as a short term solution to aid in the ‘management’ of their stress 38 . However, despite concerns of a potential deterioration in stress, studies have found that even among highly dependent smokers, stopping smoking is not associated with any long term increases in perceived stress 11 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that 33% of high school students reported involvement in physical fights in 2011, with 12% of such fights occurring on school property (Eaton et al, 2012). Fighting is associated with other high-risk behaviors including early sex, substance use, and lower academic achievement (Dukarm, Byrd, Auinger & Weitzman, 1996; Fraga, Ramos, Dias & Barros, 2011; Howard, Wang & Yan, 2007, 2008; Pickett et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are also other factors such as residence distance were far away from health care facilities, marital status and the presence of children to be cared for. The financial problem tends to be the main burden of cancer patients (Vahidi et al, 2016), in line with Kaplan, Madden, Mijanovich, and Purcaro (2013) that explained of stressor in weak economic community group which one of them was overcome with helped by the coadministered funds between government and private parties (Moffat, Noble & White, 2012). The conditions become problem associated with early treatment for breast cancer patients within the family that can lead to the quality of life of patients and caregiver (family).…”
Section: "Yes… That Time Delay Happened So Its Delay About Two Monmentioning
confidence: 81%